Fe2O3 / Nd composite photo-anode and preparation method thereof

By doping Nd element on the Fe2O3 photoanode, the Fe2O3/Nd composite photoanode is constructed, which solves the problem of limited performance of Fe2O3 photoelectro-catalytic decomposition of water, and achieves a significant increase in photogenerating current and carrier concentration.

CN119877018AActive Publication Date: 2025-04-25TIANJIN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510061311.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The performance of Fe2O3 photoelectro-catalytic decomposition of water is limited by its poor physical behavior such as high-density surface defects, fast hole recombination and short diffusion length, resulting in its low photoelectro-catalytic activity.

Method used

By performing cation replacement in a negative pressure tube furnace and using NdCl3 as the displacement source, the Fe2O3 photoanode is doped to construct the Fe2O3/Nd composite photoanode to reduce the internal impedance and increase the carrier concentration.

Benefits of technology

The performance of Fe2O3 photoanode has been significantly improved, the photogenerating current intensity has doubled, the carrier concentration has been improved, the internal resistance of the semiconductor has been reduced, and the efficiency of photoelectro-catalytic decomposition of water has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877018A_ABST
    Figure CN119877018A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photoelectrocatalysis, and discloses a Fe2O3 / Nd composite photoanode and a preparation method thereof.The preparation method comprises the steps that FTO conductive glass is put into an aqueous solution prepared from FeCl3. 6H2O and CH4N2O, and a FeOOH film growing on FTO is obtained through a hydrothermal method; calcining at a high temperature to obtain a Fe2O3 electrode; and placing the prepared Fe2O3 electrode in a negative pressure tube furnace, and carrying out replacement by taking NdCl3 as a replacement source to obtain the Fe2O3 / Nd photo-anode. According to the invention, surface metal cation replacement is carried out at high temperature to form a small amount of Nd element doping, the original iron oxide crystal structure is not damaged, the Fe2O3 / Nd composite photo-anode with coexisting Nd and Fe double metal elements is formed, the internal impedance of a semiconductor is reduced, the carrier concentration is improved, and the effective improvement of photo-generated current is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoelectrocatalysis, and in particular relates to a composite photoanode and a preparation method thereof. Background Art

[0002] Modern industrialization has intensified resource development and caused irreversible ecological damage. Hydrogen energy, as a new type of energy, is green and pollution-free, and has become one of the most promising clean energy sources in the 21st century. Modern ways to produce hydrogen energy include fossil fuel hydrogen production, biohydrogen production, water electrolysis and other methods. Photoelectrocatalytic (PEC) decomposition of water to produce hydrogen as an emerging method has gradually gained favor. In 1839, Edmond Becquerel immersed two identical metal electrodes coated with silver halide particles in a dilute acid solution and found that current was generated by irradiating them with light; in 1966, Gerischer studied the electrochemical and photoelectrochemical properties of the semiconductor / electrolyte contact interface; in 1972, Fujishima and Honda proved that TiO 2 The photoelectrode can decompose water to produce hydrogen under ultraviolet light, which has led to a deeper understanding of PEC water decomposition. After that, many oxide semiconductors were widely studied and found to have photoelectrocatalytic activity, such as TiO 2 、SrTiO 3 , ZnO and other wide bandgap semiconductors and BiVO 4 , WO 3 , Fe 2 O 3 Narrow bandgap semiconductors such as Fe 2 O 3 As a transition metal oxide semiconductor, it is abundant, non-toxic, photochemically stable, thermodynamically stable, has an appropriate band gap (1.9-2.2 eV) and a theoretical solar-to-hydrogen (STH) efficiency of 15.3%, is cheap and readily available, and has good chemical stability. It has become a research hotspot in the field of photovoltaic energy conversion in recent decades. 2 O 3 There are undesirable physical behaviors such as fast hole recombination velocity (~10ps), short hole diffusion length (2~4nm), high density of surface defects, and low oxygen evolution reaction (OER) activity. Therefore, it is very important to study reasonable and effective methods to reduce defects and improve the performance of photoelectrocatalytic water splitting. Summary of the invention

[0003] The present invention uses an element doping method to dope Fe 2 O 3 The surface layer of the photoanode is modified by adding a replacement source in a negative pressure tube furnace to replace cations and construct a composite photoanode, which reduces Fe 2 O 3The internal impedance increases the carrier concentration and improves the performance of photoelectrocatalytic water splitting.

[0004] In order to achieve the above-mentioned object of the invention, the present invention is implemented by the following technical solutions:

[0005] The present invention provides a Fe 2 O 3 / Nd composite photoanode, prepared according to the following method:

[0006] S1: Place the conductive matrix into FeCl 3 6H 2 O and CH 4 N 2 O prepared aqueous solution, the FeOOH film grown on the conductive substrate was obtained by hydrothermal method; then calcined at high temperature to obtain Fe 2 O 3 electrode;

[0007] S2: Fe obtained from S1 2 O 3 The electrodes were placed in a negative pressure tube furnace and heated with NdCl 3 As the replacement source, Fe 2 O 3 / Nd photoanode.

[0008] According to one aspect of the present invention, there is provided a Fe 2 O 3 The preparation method of the Nd / Nd composite photoanode is carried out according to the following steps:

[0009] S1: Place the conductive matrix into FeCl 3 6H 2 O and CH 4 N 2 O prepared aqueous solution, the FeOOH film grown on the conductive substrate was obtained by hydrothermal method; then calcined at high temperature to obtain Fe 2 O 3 electrode;

[0010] S2: Fe obtained from S1 2 O 3 The electrodes were placed in a negative pressure tube furnace and heated with NdCl 3 As the replacement source, Fe 2 O 3 / Nd photoanode.

[0011] In the above Fe 2 O 3 / Nd composite photoanode and preparation method thereof:

[0012] Furthermore, in S1, FeCl 3 6H 2 O and CH 4 N 2 The molar concentration ratio of O is 1:(1-1.5); CH 4 N 2 O can provide a suitable alkaline environment for the growth of FeOOH crystals; FeCl 3 6H 2 O and CH 4 N 2 Reasonable ratio can better ensure the uniformity of morphology and growth density.

[0013] Furthermore, in S1, the temperature of the hydrothermal method is 90-110°C and the time is 5-7h; this can provide the crystal with a suitable growth temperature and sufficient growth time, resulting in better crystallinity.

[0014] Furthermore, in S1, the high temperature calcination process is: first maintain at a temperature of 500-600°C for 1-2 hours, and then maintain at a temperature of 700-800°C for 5-30 minutes; selecting an appropriate temperature can ensure better crystallinity.

[0015] Furthermore, from 500-600℃ to 700-800℃, maintain 15-20℃min -1 The heating rate.

[0016] Among them, the preferred S1, Fe 2 O 3 The morphology is nanorods.

[0017] The present invention uses Nd for cation replacement, which belongs to a method of improving the performance of semiconductor photoanode by doping in the study of photoelectrocatalytic water decomposition. This method uses the high temperature and certain pressure nitrogen atmosphere protection in a tube furnace to replace the position of Nd ions and Fe ions, without destroying the structure of the crystal itself, reducing the internal impedance of the semiconductor, increasing the carrier concentration, and thus improving the photocurrent.

[0018] Furthermore, in S2, the heating rate of the negative pressure tube furnace is 5-10°C min -1 ; The appropriate heating rate can ensure the accuracy of temperature control of the negative pressure tube furnace.

[0019] Furthermore, in S2, the insulation temperature of the negative pressure tube furnace is 540-580°C, and the insulation time is 5-10 minutes; reasonable insulation temperature and insulation time can ensure the reliability and accuracy of the results.

[0020] Furthermore, in S2, the negative pressure of the negative pressure tube furnace is 200-500 Pa.

[0021] The beneficial effects of the present invention are:

[0022] (I) The present invention can ensure the conversion of FeOOH to Fe by optimizing the preparation process parameters 2 O 3 Rapid crystallization to obtain Fe with good morphology 2 O 3 Photoanode;

[0023] (ii) The present invention uses a negative pressure tube furnace to carry out cation replacement to form a composite photoanode doped with Nd element, which is different from forming a precursor for in-situ doping. By adjusting the insulation temperature and insulation time of the negative pressure tube furnace, the performance of the photoanode is improved by a small amount of cation replacement;

[0024] (IV) The preparation method adopted by the present invention does not destroy the original crystal structure, maintains the stability of the photoanode, and only replaces the surface, showing a relative improvement of pure Fe 2 O 3 The performance of the photoanode is doubled. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 (a), (b), and (c) are FeOOH and Fe prepared in Example 1. 2 O 3 , Fe 2 O 3 / Nd scanning electron microscope (SEM) image;

[0026] Figure 2 (a) and (b) are Fe prepared in Example 1. 2 O 3 Transmission electron microscopy (TEM) images;

[0027] Figure 3 (a) and (b) are Fe prepared in Example 1. 2 O 3 / Nd transmission electron microscope (TEM) image;

[0028] Figure 4 Fe prepared in Example 1 2 O 3 Line scan image of a single nanorod of / Nd;

[0029] Figure 5 (a) and (b) are Fe prepared in Example 1. 2 O 3 , Fe 2 O 3 / Nd energy spectrum (EDS) diagram;

[0030] Figure 6 (a) Fe prepared in Example 1 2 O3 , Fe 2 O 3 / Nd total X-ray photoelectron spectrum (XPS) graph, (b) is the X-ray photoelectron spectrum (XPS) graph of Nd3d;

[0031] Figure 7 The current-voltage (JV) curves of different parameters of Comparative Example 1 and Comparative Example 2 are shown;

[0032] Figure 8 Fe 2 O 3 , Fe 2 O 3 / Nd current-voltage (JV) curve;

[0033] Fig. 9 Fe 2 O 3 , Fe 2 O 3 / Nd electrochemical impedance spectroscopy (EIS) graph;

[0034] Fig.10 Fe 2 O 3 , Fe 2 O 3 Mott-Schottky plot of / Nd. DETAILED DESCRIPTION

[0035] The following is a more detailed description of the specific implementation of the present invention in conjunction with the accompanying drawings and embodiments, so as to better understand the scheme of the present invention and its advantages in various aspects. It should be noted that the specific implementation methods and embodiments described below are only for the purpose of illustration, and are not intended to limit the present invention.

[0036] Example 1

[0037] The Fe 2 O 3 The preparation method of / Nd comprises the following steps:

[0038] Step 1: Add 1.1g to 1.3g FeCl 3 6H 2 O, 0.2-0.3 g CH 4 N 2 O was dissolved in 30 ml of deionized water to form a mixed solution with a concentration ratio of 1:1, and then FTO (fluorine-doped tin dioxide) conductive glass was placed in the solution and placed in a blast drying oven for hydrothermal insulation at 100°C for 6 hours. After the reaction was completed, light yellow FeOOH grown on FTO was obtained, and the sample FeOOH was rinsed with deionized water and dried;

[0039] Step 2: Place the dried sample in a muffle furnace, calcine at 550°C for 2h, continue to heat up to 800°C, keep warm for 5min, and then naturally cool to room temperature to obtain Fe 2 O 3 Photoanode;

[0040] Step 3: Fe 2 O 3 The photoanode was placed in a quartz boat and placed in the head area of ​​the negative pressure tube furnace. 0.2 g NdCl was placed in the tail area of ​​the negative pressure tube furnace. 3 It is a displacement source, and the distance between them is 10cm.

[0041] The internal pressure of the tube was reduced to about 8Pa, and the temperature was increased from room temperature to 10℃min in a 300Pa nitrogen atmosphere. -1 The mixture was heated to 560℃ and calcined for 5min, then cooled naturally to room temperature to obtain Fe 2 O 3 / Nd composite photoanode.

[0042] Comparative Example 1

[0043] Comparative Example 1: Fe 2 O 3 / Nd photoanode, the preparation method thereof comprises the following steps:

[0044] Fe 2 O 3 The photoanode is placed in a quartz boat and placed in the head area of ​​the negative pressure tube furnace, replacing the source NdCl 3 Placed in the tail area of ​​the negative pressure tube furnace, the spacing is 10 cm, and the nitrogen pressure value, heating rate, and holding time are maintained the same as in Example 1, and the maximum temperature is changed to 540° C. and 580° C. The subsequent experimental steps are the same as in Example 1 and will not be repeated here.

[0045] Comparative Example 2

[0046] Comparative Example 2: Fe 2 was prepared in a negative pressure tube furnace with the same insulation temperature and different insulation times. 2 O 3 / Nd photoanode, the preparation method thereof comprises the following steps:

[0047] Fe 2 O 3 The photoanode is placed in a quartz boat and placed in the head area of ​​the negative pressure tube furnace, replacing the source NdCl 3 Place them in the tail area of ​​the negative pressure tube furnace with a spacing of 10 cm. Keep the same nitrogen pressure value, heating rate and maximum temperature as in Example 1, and change the insulation time to 1 min, 10 min and 30 min.

[0048] Characterization and testing

[0049] The FeOOH and Fe 2 O 3 , Fe 2 O 3 / Nd photoanodes were characterized by scanning electron microscopy (SEM), as Figure 1 (a), (b), and (c) are shown. Figure 1 (a) It can be seen that the FeOOH formed by hydrothermal treatment is dispersed in a rectangular shape and grows evenly, with a length and width of about 60nm. Figure 1 (b) It can be seen that Fe 2 O 3 Different from the rectangular shape of FeOOH, it becomes rod-shaped, grows evenly, and the gaps between nanorods become larger. This is because the crystallized H 2 O volatilization is formed, which is conducive to the transfer of photogenerated carriers; Figure 1 (c) It can be seen that the Fe 2 O 3 The / Nd photoanode did not change its dispersion state and did not collapse, which benefited from the advantages of high-temperature firing in a muffle furnace and good stability.

[0050] The Fe prepared in Example 1 2 O 3 , Fe 2 O 3 / Nd photoanode was characterized by transmission electron microscopy (TEM), and it can be seen Figure 2 Fe in (a) and (b) 2 O 3 The lattice spacing of the (104) crystal plane is 0.27nm. Figure 3 Fe in (a) and (b) 2 O 3 The lattice spacing of the (006) crystal plane of Nd is 0.23nm, and a small amount of Nd doping will not affect the Fe 2 O 3 Lattice structure.

[0051] The Fe prepared in Example 1 2 O 3 / Nd photoanode for single nanorod line scanning, Figure 4 It can be seen that in addition to Fe and O elements, there is a small amount of Nd element, which confirms the feasibility of the cation replacement experiment.

[0052] The Fe prepared in Example 1 2 O 3 , Fe 2 O3 / Nd was characterized by EDS and the elemental composition was analyzed. Figure 5 (a) We know that Fe and O elements exist. Figure 5 In (b), in addition to Fe and O, Nd also appears, indicating that Nd has been successfully replaced by Fe. 2 O 3 Photoanode.

[0053] The Fe prepared in Example 1 2 O 3 , Fe 2 O 3 / Nd was characterized by X-ray photoelectron spectroscopy (XPS). Figure 6 (a) is the XPS overall image. Figure 6 The peak of Nd can be observed in (b), indicating that Nd is successfully replaced by Fe. 2 O 3 middle.

[0054] The Fe prepared in Example 1 2 O 3 , Fe 2 O 3 The photoelectric performance of the / Nd photoanode was tested using a three-electrode system, with the prepared photoelectrode as the working electrode, the platinum sheet as the counter electrode, the saturated (KCl) Ag / AgCl electrode as the reference electrode, and the electrolyte solution as a 1 mol / L NaOH aqueous solution. A Coster electrochemical workstation was used to simulate sunlight using a Perfek PLS-FX300HU high uniformity integrated xenon lamp light source equipped with an AM 1.5G filter. The incident light power intensity was set to 100 mW cm on the surface of the working electrode. -2 The battery was calibrated with a battery detector and the test method was linear scan cyclic voltammetry with a scan rate of 20 mV s -1 .

[0055] Figure 7 The test parameters were selected for the above comparative examples 1 and 2. By comparing different parameters many times, the best experimental parameters were selected, with a temperature of 560° C. and a holding time of 5 min.

[0056] Figure 8 JV curves before and after replacement, and Fe 2 O 3 In comparison, Fe 2 O 3 / Nd photoanode at 1.23V vs.RHE potential, the photogenerated current increased from the original 0.4mA·cm -2 Increased to 0.9 mA cm -2 , the performance has doubled.

[0057] Fig. 9 The electrochemical impedance spectroscopy (EIS) diagram before and after replacement is shown in Figure 2. 2 O 3 In comparison, Fe 2 O 3 The semicircle of the Nd / Nd photoanode becomes smaller, indicating that the successful replacement of Nd reduces the internal resistance of the semiconductor, which is conducive to the faster separation and transport of photogenerated carriers.

[0058] Fig.10 The Mott-Schottky diagram before and after substitution shows that Fe 2 O 3 with Fe 2 O 3 / Nd are both n-type semiconductors. After substitution, the slope of the curve decreases, indicating that the carrier concentration increases, which also confirms the successful substitution of Nd.

[0059] It can be seen that the present invention has 2 O 3 Based on the innovative doping method, Fe 2 O 3 The electrode and the replacement source replace the surface metal cations at high temperature to form a small amount of Nd element doping, without destroying the original iron oxide crystal structure, forming a Fe2O3 with coexistence of Nd and Fe bimetallic elements. 2 O 3 The Nd / Nd composite photoanode reduces the internal impedance of the semiconductor, increases the carrier concentration, and effectively improves the photogenerated current.

[0060] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms of specific changes without departing from the scope of protection of the invention and the claims, all of which fall within the scope of protection of the present invention.

Claims

1. A method for preparing a Fe2O3 / Nd composite photoanode, characterized in that: Follow these steps: S1: placing a conductive substrate in an aqueous solution of FeCl3·6H2O and CH4N2O, and obtaining a FeOOH film grown on the conductive substrate by a hydrothermal method; and then calcining at a high temperature to obtain a Fe2O3 electrode; S2: The Fe2O3 electrode prepared in S1 is placed in a negative pressure tube furnace and replaced with NdCl3 as a replacement source to obtain a Fe2O3 / Nd photoanode.

2. The method for preparing a Fe2O3 / Nd composite photoanode according to claim 1, characterized in that: In S1, the molar concentration ratio of FeCl3·6H2O to CH4N2O is 1:(1~1.5).

3. The method for preparing a Fe2O3 / Nd composite photoanode according to claim 1, characterized in that: In S1, the temperature of the hydrothermal method is 90-110°C and the time is 5-7h.

4. The method for preparing a Fe2O3 / Nd composite photoanode according to claim 1, characterized in that: In S1, the high temperature calcination process is: firstly maintaining the temperature at 500-600°C for 1-2 hours, and then maintaining the temperature at 700-800°C for 5-30 minutes.

5. The method for preparing a Fe2O3 / Nd composite photoanode according to claim 4, characterized in that: From 500-600℃ to 700-800℃, maintain 15-20℃min -1 The heating rate.

6. The method for preparing a Fe2O3 / Nd composite photoanode according to claim 1, characterized in that: In S1, the morphology of Fe2O3 is nanorods.

7. The method for preparing a Fe2O3 / Nd composite photoanode according to claim 1, characterized in that: In S2, the heating rate of the negative pressure tube furnace is 5~10℃min -1 .

8. The method for preparing a Fe2O3 / Nd composite photoanode according to claim 1, characterized in that: In S2, the insulation temperature of the negative pressure tube furnace is 540-580°C, and the insulation time is 5-10 minutes.

9. The method for preparing a Fe2O3 / Nd composite photoanode according to claim 1, characterized in that: In S2, the negative pressure of the negative pressure tube furnace is 200 to 500 Pa.

10. A Fe2O3 / Nd composite photoanode, characterized in that: The photoanode is obtained by the preparation method of the Fe2O3 / Nd composite photoanode described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for growing rare-earth ferrite magneto-optical crystal

    CN101545133A

  • Preparation method and application of metal boride / phosphide modified alpha-Fe2O3 photo anode material

    CN107313064A

  • Preparation method of ZnO (at) Nd2O3 (at) alpha-Fe2O3 nanotube array and application of ZnO (at) Nd2O3 (at) alpha-Fe2O3 nanotube array in photoelectrocatalysis

    CN117051430A

  • Borate loaded alpha-Fe2O3 photo-anode as well as preparation method and application thereof

    CN119243232A

  • Fabrication method of a solar cell

    KR101894413B1